Exploring the role of WeChat in educational communication: Factors, usage patterns, and optimization strategies for e-learning in China - Liu, Lusi; Rungsrisawa, Somdech (Edelweiss Applied Science and Technology, 2025)
This study examines the role of WeChat in educational communication, focusing on factors influencing its adoption, usage patterns, and optimization strategies for e-learning in China. Adopting a mixed-methods approach, we combined quantitative surveys (N=398) with qualitative interviews (n=9 experts) to analyze key variables, including perceived usefulness, ease of use, content quality, and social influence. Quantitative findings, analyzed via structural equation modeling (SEM), revealed that perceived usefulness and satisfaction were the strongest predictors of continuance intention, while qualitative insights highlighted WeChat’s functional utility and social learning dynamics, alongside challenges like information overload. The study confirms WeChat’s effectiveness as a versatile educational tool but underscores the need for improved content curation and user training to mitigate platform limitations. The findings contribute to the literature on mobile learning by integrating the Technology Acceptance Model (TAM) and Expectation-Confirmation Model (ECM) within a social media-based educational context. Practical implications suggest that institutions should leverage WeChat’s accessibility while addressing pedagogical constraints through structured content delivery and digital literacy programs. Future research could explore generational differences in adoption and the long-term sustainability of social media-integrated e-learning.